(3GdfXQjI GdMOjKI ai GdGdJRGe GdWHjYi ebGQfI HGdTQjYI GdESdGejI (B/ s - (3TQa GdOjf Cejf CHhGdeLO eMeOs; (3eMeO TcQi SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JgOa gPg GdOQGSI Edi JSdjW GdVhA Ydi CgejI GdhGLHGJ GdNdbjI GdJi JHfi YdjgG GdfXQjI GdMOjKI ai GdGdJRGe GdWHjYi h eMGhdI GdGQJbGA HgPg GdhGLHGJ ddONhd ai eUGa GdGdJRGeGJ GdeOfjI GdcGedI Yf WQjb JCUjd ebJQM ddfXQjI GdMOjKI jQJcR Ydi CSGS Ndbi(B: (3h bO GYJeOJ GdOQGSI Ydi Tbjf(B: (3Tb JbdjOi jYQV GdfXQjI GdJbdjOjI GdJi bGeJ YdjgG fXQjI GdGdJRGe GdWHjYi ai GdHOGjI eY HjGf YjhHgG h GdfXQjI GdMOjKI h GdCSGS GdNdbi GdPi bGeJ Ydjg GdfXQjI GdMOjKI eY OQGSI JWHjbjI hGajI h Tb MOjK h gh eMGhdI JMOjK fXQjI GdGdJRGe GdWHjYi dci JJdGAe eY GdChVGY GdSGFOI OGNd GdeLJeY eY VQhQI GdJhGab Hjf GdbGYOI GdbGfhfjI h GdbGYOI GdNdbjI ai GdCSGS s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2016(3, bSe GdbGfhf GdeOfjs
(3HHdjhLQGajG(B: (3UaMGJ (B800-855s
Keywords: (3GdGdJRGe GdWHjYjs; (3GdGdJRGe ai GdTQjYg GdESdGejgs; (3GdGdJRGe GdWHjYi heUGOQg ai GdbGfhf GdeOfi hGdTQjYg GdGSdGejgs; (3fTGg fXQjg GdGdJRGe GdWHjYis; (3JWhQ fXQjg GdGdJRGe GdWHjYis; (3NUGFU GdGdJRGe GdNdbis; (3bhGYO GdJbGdjO hGdeLGedGJs; (3hGLH GdYWa s; (3GdGeQ HGdeYQha hGdfgi Yf GdefcQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs